Peningkatan Public Speaking bagi Siswa SMK Bina Nusa Slawi - Syaefani Arif Romadhon; Iin Indrayanti; Mutiarawati Mutiarawati (Universitas Muhammadiyah Semarang, 2021)
The activity of speaking or known as public speaking is a scary thing for students. Although they are often asked to practice presentations in front of the class, the technique of delivering public speaking is often not paid attention to. There are several techniques that should be mastered in public speaking so that the delivery can be conveyed well to the audience. This time, the implementation of PKM aims to provide knowledge about public speaking skills, improve speaking skills, mentally prepare students to speak in front of crowds, and equip students to enter lectures or work. The method presented in this activity is lecture and practice.with 20 students from SMK Bina Nusa Slawi. Students are also provided with modules to make it easier when delivering and students can also repeat the material at home. Students are also given directions regarding the correct way of presentation in Indonesian and English in accordance with the rules of public speaking. In addition to theory and practice in the classroom. Students are also directed to observe several public speaking figures through Youtube channel. In general, community service activity at SMK Bina Nusa Slawi are going well. Students' enthusiasm is extraordinary, as evidenced by the fact that 80 percent of students believe that having public speaking skills and increasing self-confidence are important. Students feel helped by this activity because they gain knowledge about public speaking and presentation techniques that can be used to support presentations in class or as a provision for later in the world of work.